Hoàn thiện công tác quản lý ngân sách phường, xã của thành phố Đà Nẵng - Nguyễn, Thanh Sang (2011)
Tác giả: Nguyễn Thanh Sang, CN; Nguyễn Hậu, CN; Nguyễn Thanh Tâm; Hồ Văn Vĩnh -- Từ khóa: Quản lý; Ngân sách; Phường; Xã; Đà Nẵng; Quản lý Nhà nước